Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Cerita Matematika Pada Siswa Smp - Kartikasari, Respina, Masduki, S.Si, M.Si (2017)
This study aims to determine the difficulties and causal factors experienced by students in solving the story roblems in the daily test of mathematics. This research is scriptive qualitative research. The subjects of this study are tudents of class VIII F SMP Negeri 1 Geyer, amounting to 32 tudents. Methods Data collection used in this study are observation, test, interview and documentation. Technique of dataanalysis through flow method consist of data collecting, data uction, presentation stage, and conclusion result of esearchindicate that as much as 32,8% student difficulties apply concept especially in differentiating domain and kodomain, 6,25% student do not experience difficulties Significant in the process of calculating the material relationships and functions, and 50% of students difficult to solve the story because students do not understand the purpose of the given problem. The difficulties students experience are caused by external factors such as: the use of improperly used teacher learning methods, the lack of teacher habits to provide practice of various story problems, and the lack of clarity of teachers in explaining the material in the classroom.